Self-Management Techniques in Managing Time Strategies for MSMEs Affected by PPKM Covid 19 - Silfani Aprianingsih; Kheryadi Kheryadi (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Self-management techniques can be used to improve behavior, control self, and time management strategies of entrepreneurs. The implementation program is carried out in Ciujung Damai Kragilan Housing with large traders. Activities are carried out with licensing for MSMEs (micro, small and medium enterprises) affected by the Covid-19 PPKM. This activity is carried out using stages such as self-observation, self-evaluation, giving reinforcement, and behavior. The programs in this activity are observation, interviews, and data collection. Research time is for 1 month. The number of MSME entrepreneurs that will be studied is 3 people. The achievements in this study were greatly improved with self-management techniques. The use of techniques by MSME entrepreneurs is more useful and time is not wasted. Strategic management in self-management techniques is able to make MSMEs gain good self-control. The effectiveness of the time set can run efficiently. And change life to the maximum than before. The recommendation used in SMEs is to use self-management techniques as the main factor in time management.